Regulatory Framework and Implementation Gap: Determinants of Micro Waqf Bank Establishment in Banten Province, Indonesia - MUHAMAD FAUZI; Royani; Iwan Agustiawan Fuad; Ahkmad Syafiudin; Ssonko Muhammedi (Universitas Negeri Semarang, 2026)
Micro Waqf Banks (MWBs) emerged in Indonesia in 2018 as Islamic microfinance institutions regulated under Law No. 1 of 2013 and OJK Regulation (POJK) No. 41 of 2024. Despite robust regulatory frameworks, implementation gaps persist between legislative intent and field reality in MWB establishment. This empirical legal research employs a qualitative methodology, with Analytic Network Process (ANP) analysis, to examine the determinants of successful MWB establishment in Banten Province, Indonesia, and to highlight discrepancies in regulatory implementation. Nine expert informants from regulatory bodies (OJK, BWI), Islamic banking practitioners (BSI Maslahat), academics, and MWB operators participated via snowball sampling. Findings reveal that motivation (spiritual-economic drive) dominates establishment success, with a weight of 0.80, vastly exceeding the influence of regulatory support, technical capacity, infrastructure, human resources, trust, and assessment factors (each 0.03-0.04). The study identifies four critical regulatory gaps: (1) absence of enforcement mechanisms linking founding motivation to operational sustainability; (2) insufficient normative clarity on nazir (trustee) accountability structures; (3) disconnection between policy objectives and institutional capacity requirements; and (4) lack of post-establishment motivation monitoring protocols. These gaps explain suboptimal MWB performance despite favourable legislation. The research demonstrates that while regulatory frameworks establish the legal foundations for MWB operations, the success of policy implementation fundamentally depends on stakeholder motivation rather than on structural-technical factors alone. This mismatch reveals a compliance deficit in Indonesia's Islamic finance regulatory architecture. Implications address both legal policy design and institutional enforcement mechanisms to bridge the motivation-structure asymmetry in Islamic microfinance governance. The study further evaluates the extent to which MWB practices comply with existing regulatory frameworks, revealing a distinction between formal compliance and substantive regulatory effectiveness.